An analysis of place value content in the Curriculum 2013 thematic textbooks for grades 1 and 2 - Salsabila Shiellany; Budi Poniam (Program Studi Pendidikan Matematika Program Pascasarjan Universitas Negeri Yogyakarta, 2020)
Textbooks play a key role in teaching mathematics in many Indonesian classrooms. Therefore, the Indonesian Ministry of Education and Culture provides textbooks for use in schools to support the teaching and learning process in the classroom. In implementing the Curriculum 2013 (Kurikulum 2013) in elementary schools, the textbooks were designed and developed by integrating various competencies and subjects, including mathematics, into several themes. This study aimed to describe the place value content in students’ thematic textbooks for elementary school students in grades 1 and 2. A descriptive qualitative method in the content analysis was conducted by focusing on three areas of analysis: six critical skills of learning place value, stages development, and strategies in teaching place value. Some findings showed that the thematic textbooks for grades 1 and 2 covered almost all skills except mentioning numbers in other forms (rename), the material presented has developed according to students’ learning development, and has implemented all strategies in teaching place values.